Some reflections on poverty eradication, true development and sustainability within CST - Juan Sapena; Vicent Almenar; Andreea Apetrei; María Escrivá; María Gil (Journal of Innovation & Knowledge, 2018)
Poverty eradication has been repeatedly identified as the largest challenge facing international society in its quest for a peaceful, prosperous, and just world.The present document summarizes academic reflections on the links between the concepts of poverty, development and sustainability. Departing from Catholic Social Teaching documents, we study how, in addition to income poverty, institutional aspects and lack of values impede severely to avoid the so-called “poverty trap”. JEL classification: A13, D63, D64, F66, Keywords: Poverty, Development, Common good, Sustainability